2020
DOI: 10.1007/s10549-020-05752-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic potential of automated Ki67 evaluation in breast cancer: different hot spot definitions versus true global score

Abstract: Purpose The proliferation-associated biomarker Ki67 has potential utility in breast cancer, including aiding decisions based on prognosis, but has unacceptable inter-and intralaboratory variability. The aim of this study was to compare the prognostic potential for Ki67 hot spot scoring and global scoring using different digital image analysis (DIA) platforms. Methods An ER+/HER2− breast cancer cohort (n = 139) with whole slide images of sequential sections stained for hematoxylin-eosin, pancytokeratin and Ki67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
0
30
0
1
Order By: Relevance
“… 16 As an effort to overcome some of these concerns, digital image analysis platforms have been developed and validated. 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“… 16 As an effort to overcome some of these concerns, digital image analysis platforms have been developed and validated. 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…This recommendation is further supported by their phase‐3 trial, where the global scoring methods showed better interobserver reproducibility compared to scoring hotspots only [5, 13, 18]. Recently, Robertson et al, reported that automated global Ki67 scoring was a more practical method and demonstrated clinical validity when compared to hotspot scoring [19]. In our study, although the visual scoring app had a feature for hotspot scoring, following recent evidence that global scores are superior to hotspot scores, we focussed only on global scoring.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of hotspots for image analysis in our study; studies have found that hotspot analysis to outperform global scoring. Robertsona et al found that hotspot scoring had double the potential for predicting recurrence free survival, in the setting of Ki-67 immunohistochemistry and breast cancer 24 .…”
Section: Discussionmentioning
confidence: 99%